Hi there!
First you simplify.
Simplified = 9x+(−5)+(−8)+x
Then you combine the like terms.
<span><span><span><span><span>9x</span>+(<span>−5)</span></span>+(<span>−8)</span></span>+x (*-5 and -8 are like terms) (9x and x are like terms)
</span></span><span><span><span>Combined it's~ (<span><span>9x</span>+x</span>)</span>+<span>(<span><span>−5</span>+<span>−8</span></span>)
</span></span></span><span><span><span>Solve and that comes to 10x</span>+<span>−<span>13 which is your answer. :)
Hope this helps.
</span></span></span></span>
Answer:
2 (4x - 1) + 6 = 8x + 4 = 4(2x+1)
Step-by-step explanation:
2 (4x - 1) + 6
= (2*4x + 2*-1) + 6
= 8x - 2 + 6
= 8x + 4
= 4/(2x+1)
15*15=225. There's only one square root of 225... there's only one square root of any number ...
Hello,
Your answer would be:
75%
Plz mark me brainliest
The answer is You are a variable